1997
DOI: 10.1159/000154851
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 gp160 Protein Modulates Proximal Tubular Cell Proliferation and Matrix Synthesis

Abstract: Cystic dilatation and tubular cell proliferation are unique features of HIV-associated nephropathy. We studied the effect of HIV-1 envelope gp160 protein on human renal proximal tubular epithelial cells (RPTEC) and opossum kidney (OK) cells. gp160 protein enhanced (p < 0.01) the proliferation of RPTEC when compared to control cells (control 9.0 ± 1.4 vs. gp160 protein 19.3 ± 2.0 × 104 cells/ml). Similarly, gp160 protein stimulated (p < 0.001) the proliferation of OK cells. This effect of gp160 was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…These include activated production and expression of growth factors (Gibellini et al 1994) and cytokines (Cupp et al 1993; Nabell et al 1994; Sastry et al 1990) and of cytokine receptors (Ganju et al 1998; Pocsik et al 1992; Puri and Aggarwal 1992), stimulation of cell proliferation and migration (Albini et al 1996b; Singhal et al 1995) and protease production, chemoattractant activity of monocytes (Albini et al 1998c; Huang et al 1998), and angiogenic activity (Albini et al 1994, 1995, 1996a; Barbanti-Brodano et al 1994; Corallini et al 1996). Extracellular Tat also transforms and immortalizes keratinocytes in cultures (Schuurman et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…These include activated production and expression of growth factors (Gibellini et al 1994) and cytokines (Cupp et al 1993; Nabell et al 1994; Sastry et al 1990) and of cytokine receptors (Ganju et al 1998; Pocsik et al 1992; Puri and Aggarwal 1992), stimulation of cell proliferation and migration (Albini et al 1996b; Singhal et al 1995) and protease production, chemoattractant activity of monocytes (Albini et al 1998c; Huang et al 1998), and angiogenic activity (Albini et al 1994, 1995, 1996a; Barbanti-Brodano et al 1994; Corallini et al 1996). Extracellular Tat also transforms and immortalizes keratinocytes in cultures (Schuurman et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] Studies suggest that HIV-1 glycoprotein causes apoptosis in human proximal renal tubular HK-2 cells at higher concentrations. [33][34][35] Lower concentrations of gp120 have also been reported to induce NFkB activation. [36,37] Ross et al reported that NFkB upregulates Fas receptor and ligand proteins on epithelium in diseased glomerular and tubulointerstitial compartments in human HIVAN specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Double staining by these two agents provides the percentage of live, apoptotic, and necrotic cells. [22] HK-2 cells were grown in keratinocyte-SFM media and transduced with the virus expressing gp120 and vector alone as described above. Analysis for apoptosis was performed after every 12 hrs of incubation period for three days.…”
Section: Analysis Of Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by several in vitro studies evaluating the effects of exogenous viral proteins on renal cell behavior. The direct application of purified viral proteins such as the precursor envelope polyprotein gp160 and its major surface fragment gp1207174 or Tat56,57 to renal cell cultures can induce a variety of responses relevant to HIVAN cell phenotypes. Such responses include activation of intracellular signaling cascades, loss of key differentiation proteins, proliferation, and apoptosis.…”
Section: Interpreting Data From Rodent Modelsmentioning
confidence: 99%